PENGARUH FAKTOR PSIKOLOGIS KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN (Survei pada Pelanggan Koran Malang Pos di Kecamatan Klojen dan Blimbing Kota Malang) - Halim Dwi Putra; Diah Paramita Sari (Inovbiz: Jurnal Inovasi Bisnis, 2015)
Abstract:  The  purposes  of  this  research  are  to  know  the  effect  of  motivation towards purchasing decision, to know the effect of customer’s perception towards purchasing decision, to know the effect of customer’s knowledge towards purchasing decision, to know the effect of customer’s belief and attitude towards customer satisfaction, and to know the effect of purchasing decision towards customer satisfaction.This research was a survey research. It was conducted at Klojen and Blimbim Districts Malang. Population of this research was the society of Malang City who subscribes Malang Pos newspaper. The sample was taken by probability sampling; the total number of sample was 100. The results of this research are (1) all the psychological factors of the customer take significant effect on the purchasing decision of Malang Post newspaper, (2) customer satisfaction in reading Malang Post newspaper was influenced by their purchasing decision. In conclusion, customer satisfaction and their purchasing decision were influenced by psychological factors of customer. Keywords: Customer psychological factors, purchasing decision, customer satisfaction